2017
DOI: 10.1364/ol.42.002275
|View full text |Cite
|
Sign up to set email alerts
|

Sellmeier equations, group velocity dispersion, and thermo-optic dispersion formulas for CaLnAlO_4 (Ln = Y, Gd) laser host crystals

Abstract: We studied the refractive index and dispersive properties of the tetragonal rare-earth calcium aluminates, CaLnAlO4 (Ln=Gd or Y). Sellmeier equations were derived for the spectral range of 0.35-2.1 μm. The group velocity dispersion (GVD) in CaGdAlO4 is positive at ∼1  μm, 95  fs2/mm and negative at ∼2  μm, -40  fs2/mm. The GVD values for CaYAlO4 are similar. In addition, thermo-optic coefficients, dn/dT, and thermal coefficients of the optical path were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Notwithstanding the foregoing, researchers found that the quantum defect near zero regarding Yb 3+ ions can differ significantly from host to host [26]. Additionally, tetragonal rare-earth calcium aluminate CaGdAlO 4 /CALGO is a noteworthy member because of its disordered structure [27]. So, intuitively, the combination of Yb 3+ ions and CALGO may be of great promise.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the foregoing, researchers found that the quantum defect near zero regarding Yb 3+ ions can differ significantly from host to host [26]. Additionally, tetragonal rare-earth calcium aluminate CaGdAlO 4 /CALGO is a noteworthy member because of its disordered structure [27]. So, intuitively, the combination of Yb 3+ ions and CALGO may be of great promise.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yb:CYA crystal has relatively higher specific heat capacity, which means a larger optical damage threshold, while its thermal conductivity is moderate. Recently, Loiko et al investigated the Sellmeier equations, group velocity dispersion, and thermooptic dispersion formulas of CYA laser host crystal, showing that the thermo-optic properties of CYA are slightly better than those of CGA, which makes Yb:CYA promising for powerscalable lasers [15]. Benefiting from the above-noted advantages, Yb:CYA crystal attracts increasing interest in ultrashort pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…x ; M 2 y 2m 1; 1. This consistency arises from the outstanding thermal-optical properties of Yb:CALGO [19], since thermal effects always lead to unwanted mixed modes [24]. Although HG 4;0 mode was hardly obtained by the off-axis method, it can be produced with the dual-off-axis pumping method by setting the off-axis displacements of OC and crystal at about x 1 ; y 1 ; x 2 ; y 2 −420 μm; 0; −400 μm; 0, as shown in Fig.…”
mentioning
confidence: 95%
“…Yb:CaGdAlO 4 (Yb:CALGO), as a new laser crystal with outstanding optical properties [19], has the broadest emission bandwidth ever discovered among Yb 3 -doped crystals [20,21]. It has been used in high-efficiency and femtosecond lasers [22,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation